2016
DOI: 10.1038/ja.2016.99
|View full text |Cite
|
Sign up to set email alerts
|

Allantopyrone A activates Keap1–Nrf2 pathway and protects PC12 cells from oxidative stress-induced cell death

Abstract: Keap1-Nrf2 system is known as a sensor of electrophilic compounds, and protects cells from oxidative stress through induction of various antioxidant enzymes. We found by proteomic analysis that allantopyrone A, a metabolite isolated from an endophytic fungus, upregulates the expression of proteins that are regulated by the transcription factor Nrf2. Indeed, allantopyrone A increased the antioxidant enzyme heme oxygenase-1 in PC12 cells. Moreover, it induced localization of Nrf2 in the nucleus. Affinity purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Numerous experimental results show that the oxidative stress sensor protein Keap1 and Nrf2 are closely related to the oxidative stress injury and the antioxidant response ( Uesugi et al, 2017 ; Wasik et al, 2017 ). Previous studies suggested that H 2 S played an important role in protecting against oxidative stress by enhancing Nrf2 nuclear translocation and initiating antioxidant response in ischemia-reperfusion injury ( Calvert et al, 2009 ; Guo et al, 2014 ; Shimada et al, 2015 ), diabetes-accelerated atherosclerosis ( Xie et al, 2016 ) and high salt-induced renal injury ( Huang et al, 2016 ).…”
Section: Sulfhydration Mediates H 2 S-induced Biolmentioning
confidence: 99%
“…Numerous experimental results show that the oxidative stress sensor protein Keap1 and Nrf2 are closely related to the oxidative stress injury and the antioxidant response ( Uesugi et al, 2017 ; Wasik et al, 2017 ). Previous studies suggested that H 2 S played an important role in protecting against oxidative stress by enhancing Nrf2 nuclear translocation and initiating antioxidant response in ischemia-reperfusion injury ( Calvert et al, 2009 ; Guo et al, 2014 ; Shimada et al, 2015 ), diabetes-accelerated atherosclerosis ( Xie et al, 2016 ) and high salt-induced renal injury ( Huang et al, 2016 ).…”
Section: Sulfhydration Mediates H 2 S-induced Biolmentioning
confidence: 99%